Measuring customer satisfaction with some of the controllable elements of the total retail experience: An exploratory study - N. S. Terblanche; C. Boshoff (South African Journal of Business Management, 2001)
Total retail experience is, for the purposes of this study, defined as all the elements that encourage or inhibit consumers during their contact with a retailer. This article reports on the influence of three dimensions of consumers' total retail experience on their satisfaction levels. The items used to measure the theoretical model demonstrate sufficient reliability and discriminant validity. The theoretical model is then tested using a structural equation modeling approach. Although not a test of a comprehensive model of the total retail experience, the study does shows that the personal interaction between retail employee and customer on the one hand, and physical cues on the other hand, impact strongly on customer satisfaction.
Keywords: 650